Sparkle [videorecording (DVD)] - Akil, Salim, 1964-; Houston, Whitney; Sparks, Jordin; Luke, Derek, 1974-; Epps, Mike; Ejogo, Carmen, 1974-; Sumpter, Tika (Sony Pictures Home Entertainment, 2012)
Set in the 1960s, Sparkle and her two sisters form a singing group and dream of becoming stars beyond the affluent Detroit suburb where they come from, and where they are already well-known. But as the sisters become more famous, the close-knit nature of their family begins to fall apart. Features the late Whitney Houston's final screen performance.